Morphologie und Semantik der "n"-Erweiterung bei "Muttern" und "Vatern" im Deutschen - Alexander Werth (Zeitschrift für Wortbildung)
This paper deals with German kinship terms ending with the form n (Muttern, Vatern). Firstly, data from newspapers are presented that show that especially Muttern denotes very special meanings that can only be derived to a limited extent from the lexical base: a) Muttern referring to a home where mother cares for you, b) Muttern standing for overprotection, and c) Muttern representing a special food style (often embedded in prepositional phrases and/or comparative constructions like wie bei or wie von Muttern). Secondly, it is argued that the addition of n to kinship terms is not a word-formation pattern, but that these word forms are instead lexicalized and idiomatized in contemporary German. Hence, a diachronic scenario is applied to account for the data. It is argued in the present paper that the n-forms have been borrowed from Low German dialects, especially from constructional idioms of the type ‘X-wie bei Muttern’ and that forms were enriched by semantic concepts associated with the dialect.